2019
DOI: 10.28955/alinterizbd.585219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhizobacteria on Plant Development, Quality of Flowering and Bulb Mineral Contents in Hyacinthus orientalis L.

Abstract: Size of bulbs is directly proportional to the quality of the flower, the commercial value of the bulb and getting more bulblet. The research was carried out to evaluate the effects of PGPR on plant growth parameters, flowering, bulb quality and bulb mineral contents in hyacinth (Hyacinthus orientalis L. cv. Aiolos) under greenhouse condition. In the study, there were 5 applications: (T1) Pseudomonas putida strain RCK-42A, (T2) Kluyvera cryocrescens strain RCK-113C, (T3) Paenibacillus polymyxa strain RCK-12E, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
2
1
Order By: Relevance
“…With the help of bacterial applications, boost in nutrient uptake, implementing plant growth hormones, raising chlorophyll content and organic acids, it is fairly possible to increase the plant growth. (Parlakova Karagöz et al, 2019). Previous studies are coherent with the present ones in this matter.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…With the help of bacterial applications, boost in nutrient uptake, implementing plant growth hormones, raising chlorophyll content and organic acids, it is fairly possible to increase the plant growth. (Parlakova Karagöz et al, 2019). Previous studies are coherent with the present ones in this matter.…”
Section: Resultssupporting
confidence: 86%
“…Unlike the other studies (Eid et al, 2009;Parlakova Karagöz et al, 2019), compared to NPK and control applications, lower values of microbial fertilizer applications in N and P intake of hyacinth leaves and bulbs were obtained. According to Çığ and Çığ (2019), the control plants demonstrated the highest value (with no bacterial application and fertilization) of the weight, length and width of hyacinth bulb (both laboratuary and field conditions), however bacterial applications had negative effects on these values.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…With the inoculation of PGPRs on Hyacinthus orientalis cv. 'Aiolos' , there had been increases in leaf width and length, number of florets, flower diameter and length, stalk thickness, bulb diameter, length and weight in greenhouse conditions [27]. It has been concluded that the bacterial formulation applications increased in the number of bulbs and quality of the tulip cultivars in the field conditions [28].…”
Section: Resultsmentioning
confidence: 95%